Medicaid Capitation Payments by State - David C. Hsia JD, MD, MPH (SAGE Publishing, 2019)
Congress has repeatedly proposed changing Medicaid from an entitlement to a block grant. Each state would receive a fixed amount instead of a Federal payment influenced by state decisions on eligibility, coverage, and pricing. This paper uses existing data series to simulate redistributing the annual $353 billion Federal payment among Medicaid's 56 state (and territorial) programs. Capitation by general population would shift $52 billion, mainly from large Northeastern and West Coast states to large Southern and Mountain states. Capitation by population below the Federal Poverty Line (FPL) would shift $60 billion in a similar pattern. Policymakers should understand likely state-to-state effects when considering Medicaid legislation. States could then prepare for possible changes in their Federal payment for Medicaid.